2013
DOI: 10.1016/j.devcel.2013.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Lamina-Associated Polypeptide-1 Interacts with the Muscular Dystrophy Protein Emerin and Is Essential for Skeletal Muscle Maintenance

Abstract: SUMMARY X-linked Emery-Dreifuss muscular dystrophy is caused by loss-of-function of emerin, an integral protein of the inner nuclear membrane. Yet emerin null mice are essentially normal, suggesting the existence of a critical compensating factor. We show that the lamina-associated polypeptide1 (LAP1) interacts with emerin. Conditional deletion of LAP1 from striated muscle causes muscular dystrophy and this pathology is worsened in the absence of emerin. LAP1 levels are significantly higher in mouse than human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
135
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(140 citation statements)
references
References 44 publications
5
135
0
Order By: Relevance
“…Constitutive knockout of LAP1 in mice causes perinatal lethality; however, a very recent study reported that the conditional deletion of LAP1 from mouse striated muscle leads to muscular dystrophy whereas LAP1 deletion from hepatocytes does not affect liver function [13,26]. This model supports the notion that LAP1B has a specific role in striated muscle and represents a functional validation of the effect of LAP1B deficiency in human striated muscle.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Constitutive knockout of LAP1 in mice causes perinatal lethality; however, a very recent study reported that the conditional deletion of LAP1 from mouse striated muscle leads to muscular dystrophy whereas LAP1 deletion from hepatocytes does not affect liver function [13,26]. This model supports the notion that LAP1B has a specific role in striated muscle and represents a functional validation of the effect of LAP1B deficiency in human striated muscle.…”
Section: Discussionsupporting
confidence: 61%
“…In contrast to LAP1 knockout mice exhibiting perinatal lethality, loss of function of LAP1B in humans appears to affect only muscle tissue, and a possible explanation is that variation in the level of expression of the different LAP1 isoforms observed in mouse and human tissue, might lead to different phenotypes in the case of loss of function of LAP1 [26]. In the presented case, only the 66.3 kDa isoform was absent in muscle fibres.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…A mutation in TOR1AIP1 encoding LAP1 has been described in two affected family members in with muscular dystrophy and cardiomyopathy [54]. LAP1 binds to lamins and emerin and its conditional deletion from muscle in mouse causes profound muscular dystrophy, cardiac dysfunction and early lethality [55,56]. Heterozygous missense mutations in TMEM43 encoding an integral inner nuclear membrane protein called LUMA have also been reported in two patients with EDMD-like phenotypes [57].…”
Section: Muscular Dystrophymentioning
confidence: 99%